A sustainable seaweed win-win: dietary fortification with Irish Wakame (Alaria esculenta) enhances Atlantic salmon (Salmo salar) muscle growth and modulates gene expression - Courtney E. Gorman; Lewis D. Taylor; Fintan Egan; Francisco Javier Alarcón-López; Philip McGinnity; C. Darrin Hulsey (Frontiers in Marine Science, 2026)
Seaweeds are increasingly being incorporated into animal diets to address the challenge of intensifying food production while minimizing ecological impacts. Although seaweeds represent promising natural resources for developing economically and environmentally sustainable feeds, especially in aquaculture, the consequences of ingesting seaweed for the animals themselves are often unclear. Therefore, this study examined how the inclusion of the brown seaweed Alaria esculenta affects body condition, skeletal muscle growth, and gene expression across three tissues in Atlantic salmon ( Salmo salar ). Dietary inclusion of A. esculenta was found to significantly enhance juvenile S. salar body condition. Then, using a novel application of contrast-enhanced soft tissue computed tomography, it was demonstrated that seaweed positively influenced the muscle cross-sectional area of the commercially valuable filet muscle. Transcriptomic analysis further revealed that dietary seaweed altered the expression of hundreds of genes, including several involved in muscle and immune function across the three tissues. These integrative findings indicate that A. esculenta enhances salmon muscle growth and influences the molecular underpinnings of fish health, collectively supporting the utility of seaweed as a sustainable win-win functional food.